The Effect of Tax Incentives and Ease of Doing Business on Foreign Direct Investment in ASEAN Member Countries - Rizka, Rahmawati; Asqolani, Asqolani (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2023)
Investment, particularly from overseas, emerges as a pivotal driver of economic expansion in Indonesia. Despite grappling with the challenges posed by the Covid-19 pandemic, foreign direct investment (FDI) inflows to Indonesia surged by 5.5% from the preceding year, reaching Rp 111.1 trillion or USD 7.92 billion in 2020. This study endeavors to scrutinize and uncover empirical evidence regarding the influence of tax incentives and the ease of conducting business on FDI flows. The study's sample encompasses ASEAN member nations, excluding Myanmar and Brunei Darussalam, spanning the period from 2010 to 2018. Tax rates, tax holiday incentives, and the Ease of Doing Business (EoDB) index serve as the independent variables in this analysis. Employing cross-border panel data, the study seeks to discern the determinants of FDI. Findings indicate that tax rates and tax holiday incentives exhibit a significant negative impact on FDI flows, while the ease of doing business exerts a notable positive influence. Governmental policies in formulating tax incentives and fostering favorable business environments endow institutional advantages, thereby bolstering investors' inclination to channel FDI into the country.